Processos interacionais em escrita coletiva de texto por alunos da 5ª série (6º ano) do ensino fundamental - Alano, Eloíse Machado de Souza (2010)
Based on Relevance Theory (SPERBER; WILSON, 1986, 1995), interactional processes in collective writing elaborated by 6th year (5th grade) students of elementary school were analyzed in this research. In order to achieve this goal, it was asked a group of four students from Escola de Ensino Básico Senador Francisco Benjamim Gallotti, Tubarão (SC) to collectively finish an incomplete narrative. The interaction was recorded in audio and video, and the textual production was analyzed. Each utterance of the text was embedded within their respective logical form, and explicatures and implicatures were elaborated when necessary. The findings corroborated the relevance of the descriptive and explanatory analysis methodology, and suggest among other observations that: a) the story was readily defined by the group, and most of the interaction time was devoted in discussing relatively successful ways of textualization, suggesting the development of negotiation and textual production skills, when compared with 2nd year (1st grade) students (SILVA, 2009); and b) the group discarded ideas which would make more complex the story, so that the final text did not adequately reflect the richness of the discussion, suggesting the use of strategies to maximizing the relevance by minimizing cognitive effort in the textualization, as in Silva (2009).